2010
DOI: 10.1159/000300388
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Attenuates Renal Hypertrophy in Early-Stage Diabetes by Activating AMPK

Abstract: Background: Recent studies suggest the involvement of the adenosine monophosphate-activated serine/threonine protein kinase (AMPK) pathway in the pathogenesis of diabetic nephropathy (DN). Resveratrol, an agent that activates AMPK, may have the potential to protect against the development of DN. This study was designed to investigate the therapeutic effects of resveratrol on renal hypertrophy in early-stage diabetes and the underlying mechanisms. Method: Molecular and structural changes involved in the pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 54 publications
(35 reference statements)
2
61
0
Order By: Relevance
“…Activating AMPK can reduce glomerular and renal tubule damage [51]. Reports have demonstrated that Res can alleviate renal damage in earlystage diabetic nephropathy by activating AMPK [52]. Therefore, the AMPK signaling pathway is a protective regulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Activating AMPK can reduce glomerular and renal tubule damage [51]. Reports have demonstrated that Res can alleviate renal damage in earlystage diabetic nephropathy by activating AMPK [52]. Therefore, the AMPK signaling pathway is a protective regulatory mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches have demonstrated that the occurrence and development of type 2 diabetes and its complications are closely associated with the change of nutrient-sensitive pathways. The major related nutrient-sensitive signal proteins include mTOR [40] , AMPK [41] and oxidized coenzyme-dependent histone deacetylase (Sirt1) [42] . As nutritional conditions change (high glucose environment), nutrient signal pathways inflict damage on the autophagy functions of cells so that the cells are unable to react normally to all sorts of extracellular stress, and organelle functions are further disordered, resulting in diabetic nephropathy.…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…Both resveratrol and metformin can be used to activate AMPK. Reports have demonstrated that resveratrol can alleviate renal damage in early-stage diabetic nephropathy by activating AMPK [41] . In the glomeruli and renal tubules in animal models of type 1 and 2 diabetic nephropathy, AMPK activity is inhibited.…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…In the high glucose milieu, studies showed that AMPK phosphorylation and activity were reduced in the renal cortex of kidneys from STZ-induced diabetic rats and db/ db mice, which are models of type 1 and type 2 diabetes, respectively (9,15,36,46,75,82). AMPK activators, resveratrol (9,15,36), metformin (9,15,36,46,75,82), and 5-aminoimidazole-4-carboxamide-1b-riboside (AICAR) (46) attenuated renal hypertrophy, lipid accumulation and albumin excretion in diabetic kidneys. Thus, inhibition of AMPK activity contributes to alterations in the diabetic kidney, such…”
Section: Autophagy In Diabetic Nephropathymentioning
confidence: 99%